History of Preclinical Models of Intracerebral Hemorrhage - Ma, Qingyi (2011)
In order to understand a disease process, effective modeling is required that can assist scientists in understanding the pathophysiological processes that take place. Intracerebral hemorrhage (ICH), a devastating disease representing 15% of all stroke cases, is just one example of how scientists have developed models that can effectively mimic human clinical scenarios. Currently there are three models of hematoma injections that are being used to induce an ICH in subjects. They include the microballoon model introduced in 1987 by Dr. David Mendelow, the bacterial collagenase injection model introduced in 1990 by Dr. Gary Rosenberg, and the autologous blood injection model introduced by Dr. Guo-Yuan Yang in 1994. These models have been applied on various animal models beginning in 1963 with canines, followed by rats and rabbits in 1982, pigs in 1996, and mice just recently in 2003. In this review, we will explore in detail the various injection models and animal subjects that have been used to study the ICH process while comparing and analyzing the benefits and disadvantages of each.